Micro enterprises in Malaysia: an empirical assessment on financial obstacles - Duasa, Jarita; Mohd Thas Thaker, Mohamed Asmy; Mohamed, Mustafa Omar; Afroz, Rafia; Zainal Abidin, Rozita (2014)
This study was designed to empirically determine how and to what extent the micro enterprises in Malaysia are able to overcome the problems of accessing finance. The primary data is collected from the administered survey questions in Klang Valley (Selangor and Kuala Lumpur) and the analysis is conducted using statistical analysis and Logistic Regression analysis. It outlines an approach on how micro enterprises perceive the constraints of financial access emerge as the binding constraint. Micro enterprises are considered as risky business and thus strict loan conditions have been imposed on them by financial institutions. Among the conditions imposed by the financial institutions are strict collateral requirement, high cost of financing, strict documentation requirement and good financial and business track record. Unfortunately, most of them cannot fulfill these conditions and continue to face the problem of accessing finance. The results of the study revealed that lack of accessing to finance has hampered the development of micro enterprises in Malaysia.